Fungsi Penggembalaan Seorang Pendidik Kristen - Ni Putu Sumarmi (Jurnal Pistis: Teologi dan Praktika, 2021)
Christian education is one of the mandates that must be implemented by the church. The existence of a church phenomenon, that focuses on pastoral care has the potential to ignore the duties and roles of an educator. Likewise, an educator who focuses on the intellectual aspect has the potential to neglect his duty as a shepherd for his students. So there needs to be a balance in carrying out the duties of education and the function of shepherding. This paper notes the practical principles that a Christian educator should have. This paper attempts to provide a topical interpretation of education from the Bible and to extract opinions from Christian education experts. Thus, a Christian teacher must have spiritual, moral, intellectual and practical skills in an effort to build a spiritually mature Christian generation.